Transformation of Islamic Finance in the Digital Era: Developments and Challenges of Halal Fintech - Rindang Nuri (Generate Digital Publishing, 2025)
Objective: This study aims to examine the development of the halal fintech industry, the regulatory challenges faced, and how public perceptions of digital Islamic finance affect the adoption of these services. Research Design & Methods: This research uses a descriptive qualitative method with thematic analysis to deeply understand the phenomenon of halal fintech industry development and challenges, using secondary data from industry reports, statistical data, and relevant academic studies, to identify key themes covering regulation and consumer trust Findings: The results show that consumer trust in Islamic fintech is strongly influenced by perceived usefulness and social influence. In Indonesia, consumers are more likely to adopt Islamic fintech services because they find the technology useful and are supported by their community. In Malaysia, government support and a strong regulatory framework increase consumer trust. However, the main challenges are still related to regulation, especially sharia compliance standards and regulatory limitations that hinder innovation in some countries. Implications & Recommendations: The study recommends strengthening the regulatory framework to ensure better Shariah compliance. The government and regulatory bodies should collaborate with industry stakeholders to create an ecosystem that supports fintech innovation. Contribution & Value Added: This research contributes to the literature by providing a detailed examination of how emerging technologies can solve traditional challenges in Islamic finance, particularly regarding transparency, efficiency and consumer trust. It also offers practical recommendations to address regulatory challenges, thereby supporting the sustainable growth of halal fintech globally.